2018
DOI: 10.1002/hep.29609
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus sensitivity to interferon‐α in hepatocytes is more associated with cellular interferon response than with viral genotype

Abstract: In the cell-culture-based HBV infection models, the sensitivity of HBV to IFN-α in hepatocytes is determined more by the cell-intrinsic IFN response than by viral genotype, and improvement of the IFN response in HepG2-NTCP cells promotes the efficacy of IFN-α against HBV. (Hepatology 2018;67:1237-1252).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 50 publications
5
54
0
1
Order By: Relevance
“…Previous study revealed that the innate immune pathway was not induced in CHB patients’ liver, which could be reactivated following stimulation of Toll‐like receptor (TLR)3 by poly I:C or virus . Yuan et al also found that host factors played an important part in antiviral immunity, whereas HBV sensitivity to IFNα was more related to activation of cellular IFN pathway than the viral genotype . Because the analysis of GEO data guided us to focus on host immunity, we applied PCR array to investigate factors concerning the innate immunity against virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study revealed that the innate immune pathway was not induced in CHB patients’ liver, which could be reactivated following stimulation of Toll‐like receptor (TLR)3 by poly I:C or virus . Yuan et al also found that host factors played an important part in antiviral immunity, whereas HBV sensitivity to IFNα was more related to activation of cellular IFN pathway than the viral genotype . Because the analysis of GEO data guided us to focus on host immunity, we applied PCR array to investigate factors concerning the innate immunity against virus.…”
Section: Discussionmentioning
confidence: 99%
“…(22) Yuan et al also found that host factors played an important part in antiviral immunity, whereas HBV sensitivity to IFNα was more related to activation of cellular IFN pathway than the viral genotype. (23) Because the analysis of GEO data guided us to focus on host immunity, we applied PCR array to investigate factors concerning the innate immunity against virus. Consistently, our study demonstrated lower baseline level of IFNα mRNA in PBMCs of CHB patients with suboptimal response to IFNα treatment, whereas there was an increased baseline level of the host immune regulator, IFITM2, indicating that an impaired immune pathway may be responsible for IFNα inefficiency (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Proliferating HepaRG cells were purchased from Biopredic International (Rennes, France) and were amplified and differentiated according to the manufacturer's protocol. HepG2-NTCP (kindly provided by Yi Ni and Stephan Urban) and primary human hepatocytes (PHH; purchased from Bioreclamation IVT) were cultured as described previously (41). The human hepatomaderived cell line HepG2 (purchased from ATCC) was cultured in Dulbecco's modified Eagle medium (DMEM)/F12 supplemented with 10% fetal bovine serum (Invitrogen), 2 mM L-glutamine, 100 U/ml penicillin, and 100 mg/ml streptomycin at 37°C under humidified air that contained 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…HBV infection. HBV was prepared from the HepAD38 cells (43), and the infection was performed with 150 GE per cell in the presence of 4% (vol/vol) polyethylene glycol 8000 (PEG 8000; Sigma-Aldrich) at 37°C for 24 h, as we described previously (41). The cells were washed and maintained in medium with a medium change every 2 to 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…Interferon (IFN)-α, a type I IFN, modulates the immune response to HBV infection by activating multiple IFNstimulated genes (ISGs), which act to inhibit HBV replication by affecting multiple steps of the viral life cycle and inducing the decay of established HBV cccDNA. 3,7 IFN-γ, a type II IFN, is produced by intrahepatic cytotoxic T lymphocytes, and has non-cytolytic antiviral potential. 8,9 Using a transgenic mouse model of chronic hepatitis B, we showed that CD8 + cytotoxic T lymphocytes are primarily responsible for the induction of chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%